Efektivitas Program Kelompok Usaha Bersama (Kube) Ternak Domba Oleh Dinas Sosial Dalam Upaya Pemberdayaan Masyarakat Di Desa Bojongkunci Kabupaten Bandung - Radiansyah, Rifi Rivani; Karnita, Karnita; Septiansyah, Bayu (Jurnal Agregasi, 2025)
This research underlines the problem of the effectiveness of the Joint Business Group (KUBE) Program by the Bandung Regency social service in community empowerment efforts in Bojongkunci Village which aims to find out, analyze and to build scientific propositions regarding these research problems. the research method used is a qualitative method with a grounded theory approach. The results showed that the KUBE program has not provided effective results for related business groups or in empowering the community. The scientific findings of this research underline several important aspects that must be ensured in order for a program to run effectively to achieve the goals set by an organization, which include, understanding the program, the accuracy of program targets, the timeliness of the program, the achievement of program objectives, and real changes that can be reviewed from the existence of concrete evidence regarding community welfare, access to resources and their benefits, critical awareness, participation and social control of the community.